Sex before or after blood feeding : Mating activities of Aedes aegypti males under conditions of different densities and female blood feeding opportunities - Dieng, Hamady; Satho, Tomomitsu; Fatimah, Abang; Erida, Wydiamala; Nur Faeza, Abu Kassim; Nur Aida, Hashim; Wan Fatma, Zuharah; Tonga, Noweg (Elsevier Ltd, 2019)
Blood feeding and mating are critical behaviors that regulate both mosquito population maintenance and disease transmission. However, our understanding of mosquito mating systems remains incomplete. One of the most critical issues is a lack of understanding regarding how and where males and females encounter one another. This study was performed to investigate changes in key mating behaviors of Ae. aegypti relative to female blood feeding opportunities, taking into account male density. We compared courtship latency and copulation activity between single and pooled males in a range of assays performed in the presence or absence of a blood source and after blood feeding. The time taken by grouped males to initiate courtship in the presence of a host was much shorter than that in single males. There was no significant difference in courtship latency between pooled and single males in the absence of a blood source or after blood feeding. At low male density, the presence of the host and blood meal ingestion provided better conditions for copulation. At high male density, however, copulation activity was decreased after blood feeding, but remained high regardless of the presence or absence of the host. In addition to providing insight into the mating ecology of Aedes aegypti, this study indicated that the presence of a blood source influences how males encounter and copulate with females. The observation that copulation activity decreases after blood feeding when males are numerous provides new avenues for improving mass release programs of sterile mosquitoes.